Ethnobotanical study of Tetraclinis articulata in western Algeria: traditional uses and therapeutic potential - Nesrallah, Chaima Narimane; Bouchaour-Djabeur, Sabiha (Ethnobotany Research and Applications, 2026)
Background: This ethnobotanical survey, carried out in four wilayas of western Algeria (Bechar, El Bayadh, Tlemcen and Ain Temouchent), was based on interviews with specialists in traditional phytotherapy (herbalists and traditional healers) to identify and document the popular uses associated with Tetraclinis articulata (T. articulata), locally known as arar tree. Methods: Information was collected using a semi-structured questionnaire, enabling the investigation of the therapeutic uses of T. articulata across several clearly defined dimensions, including medical indications (ailments targeted by traditional treatments), plant parts used (leaves, wood, cones, etc.), preparation and administration methods (infusion, decoction, inhalation, external application, etc.), types of treatments practiced, and potentially reported side effects. Results: The study reveals a widespread integration of the arar tree in local folk medicine, with a usage rate of 99.09 % among participants. A total of 42 ailments were recorded, including digestive disorders (e.g., gastric ulcers), respiratory conditions (e.g., cough), and urological diseases (e.g., urinary tract infections). Two quantitative indicators confirm the importance of the species, with a Use Value (UV) of 2.7 and a Cultural Importance Index (CI) of 1.76. Conclusions: These results demonstrate the major role of T. articulata in traditional local healthcare, as well as its strong cultural value. The study highlights the richness of orally transmitted knowledge surrounding this species and emphasizes the need to integrate it into a scientific framework for the sustainable development and rational conservation of this plant resource from the Mediterranean region. Keywords: Tetraclinis articulata, Ethnobotanical survey, Traditional medicine, Therapeutic properties